(Need asap)Solve each equation. Use one of the 4 methods you have practiced the last few days:
1. Write exponents using the same base
2. Take the log of both sides
3. Use properties of logs then write as an exponent
4. Use properties of logs then drop the log on both sides

9. -7(10)^8-10x +9=4

Respuesta :

msm555

Answer:

x ≈ 0.83365

Step-by-step explanation:

To solve the equation [tex]-7 \times 10^{8-10x} + 9 = 4[/tex], we'll use the following logarithmic rule:

[tex]a \cdot b^x = a \cdot e^{x \cdot \ln(b)}[/tex]

Using this rule, we can rewrite the equation as:

[tex]-7 \cdot e^{\ln(10) \cdot (8-10x)} + 9 = 4[/tex]

Now, observe that [tex]\ln(10) = 1[/tex] because [tex]\ln(10)[/tex] is the natural logarithm of [tex]e[/tex] raised to the power of [tex]1[/tex], which is just [tex]10[/tex]. So, the equation simplifies to:

[tex]-7 \cdot e^{8-10x} + 9 = 4[/tex]

Now, we subtract 9 from both sides to isolate the exponential term:

[tex]-7 \cdot e^{8-10x} = 4 - 9[/tex]

[tex]-7 \cdot e^{8-10x} = -5[/tex]

Next, we divide both sides by [tex]-7[/tex] to isolate the exponential term:

[tex]e^{8-10x} = \dfrac{-5}{-7}[/tex]

[tex]e^{8-10x} = \dfrac{5}{7}[/tex]

Now, we take the natural logarithm of both sides to eliminate the exponential term:

[tex]\ln(e^{8-10x}) = \ln\left(\dfrac{5}{7}\right)[/tex]

[tex]8 - 10x = \ln\left(\dfrac{5}{7}\right)[/tex]

Finally, we solve for [tex]x[/tex]:

[tex]8 - 10x = \ln\left(\dfrac{5}{7}\right)[/tex]

[tex]-10x = \ln\left(\dfrac{5}{7}\right) - 8[/tex]

[tex]x = \dfrac{\ln\left(\dfrac{5}{7}\right) - 8}{-10}[/tex]

[tex] x \approx 0.8336472236621 [/tex]

[tex] x \approx 0.83365 \textsf{(in 5 d.p.)}[/tex]

Therefore, x ≈ 0.83365.

Ver imagen msm555